What constitutes ‘poor’ adherence to medical advice for chronic diseases? Insights from a qualitative study among hypertension and diabetes patients in urban informal settlements, Mumbai Metropolitan Region - Jennifer Spencer; Manjula Bahuguna; Sudha Ramani; Sweety Pathak; Sushma Shende; Shanti Pantvaidya; Vanessa D’Souza; Anuja Jayaraman (PLoS ONE, 2025)
Introduction The problem of poor adherence to medical advice in the case of non-communicable diseases, the reasons thereof, and how these are exacerbated in low- and middle-income countries (LMICs) is well-recognized. However, there is less conceptual clarity on what ‘poor’ adherence encompasses in these settings. Conventional classifications treat poor adherence as a singular category, often disregarding its multifaceted nature. This study aimed to explore the nuances of what constitutes ‘poor’ adherence to medical advice for chronic diseases in vulnerable LMIC settings. This was done by examining the different ways in which hypertension and diabetes patients living in urban informal settlements in the Mumbai Metropolitan Region attempted to adhere to medical advice. Methods This is a qualitative study using a grounded analysis approach. The study was part of larger research conducted to understand care-seeking for hypertension and diabetes in urban informal settlements. Purposive sampling was used to identify participants. Data was collected from September to November 2022 through in-depth interviews with 26 hypertension and diabetes patients. Emerging patterns of adherence were inductively coded and categorized using grounded analysis. Findings The study highlights multiple ways in which patients attempted to adhere to medical advice. By tracing patient journeys and experiences in adherence, the study categorizes ‘poor’ adherence to medical advice as adherence to medication, lifestyle changes and follow-ups with various sub-categories within each. Most patients reported more than one way in which they tried to adhere to medical advice. Patients adhered well to some aspects of their medical advice and not to others, highlighting the complexities in understanding this concept. Conclusions By understanding the nuances and complexities of ‘poor’ adherence in urban informal settlements, the study builds an empirically grounded typology on adherence. Such a typology is useful for research and practice on improving adherence to medical advice in vulnerable LMIC settings.